Multicultural Education At Kiai Haji Achmad Siddiq Jember State Islamic University: Implementation Of James Albert Banks' Concept Of Thought - Mashudi mashudi; Zeiburhanus Saleh (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
Education is a strategic means to unify a pluralistic nation. This study aims to explore the implementation of multicultural education at the State Islamic University of Kiai Haji Achmad Siddiq (UIN KHAS) Jember based on James A. Banks' concept. The research employs a qualitative-descriptive approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis techniques involve data presentation, classification, interpretation, and triangulation for validity. The study focuses on five dimensions of multicultural education: content integration, the knowledge construction process, prejudice reduction, equity pedagogy, and an empowering school culture and social structure. The results show that UIN KHAS Jember has implemented multicultural education values in both the learning process and academic culture, particularly in creating a space for equality, respecting differences, and fostering an inclusive attitude among students. Lecturers play a crucial role in creating a learning environment that values diversity. The study concludes that multicultural education in Islamic higher education can be effectively implemented through strengthening the roles of lecturers and institutional policies.